Missing pieces of the puzzle to effectively control digital dermatitis. (10th November 2017) - Orsel, K.; Plummer, P.; Shearer, J.; De Buck, J.; Carter, S. D.; Guatteo, R.; Barkema, H. W.
Summary: Since the first report of bovine digital dermatitis (DD) in 1974, there is a large body of the literature published; however, effective prevention and control of the disease remain elusive. Although many aspects of the pathogenesis of DD have been investigated, even some of the most basic questions such as the aetiology of this disease remain under debate. Treponema spp. have been strongly associated with DD lesions and occur in abundance in advanced lesions; however, efforts to induce disease with pure cultures of these organisms have been largely underwhelming and inconsistent. Furthermore, although the disease has been presented for several decades, there is limited scientific evidence regarding effective treatment of DD. Apparent discrepancies between effectiveness in vitro and in vivo have challenged the scientific community to identify new potential treatment options. With no treatment resulting in a 100% cure rate, the current expectation is manageable control, but prospects for the eradication of the disease are unlikely using current approaches. In order to develop more effective approaches to control DD on‐farm, there is a critical need for a deeper understanding regarding the causation, ecology, transmission and treatment of this disease. In this article, we attempt to provide insights into specific research needs related to DD in order to assist the industry, researchers, pharmaceutical companies and research sponsors with decision‐making and identified research gaps.